Joachim von Braun and Rajul Pandya-Lorch (eds.). Food Policy for the Poor: Expanding the Research Frontiers: Highlights from 30 Years of IFPRI Research. Washington, D. C.: IFPRI, 2005. 253 Pages. Price not given. (The Pakistan Development Review, 2005)
The research of the past 30 years at the International Food Policy Research Institute (IFPRI) is highlighted in this volume. The topic is food and nutrition security. Of related concern are the development strategies that impact on technologies for agricultural production, resource management, conflicts and natural disasters, subsidies and safety nets, gender roles, and health. The book consists of nine chapters. The first chapter discusses a changing IFPRI in a changing world. The current and future world food situation is analysed and ways are suggested to increase agricultural production and to explore policies for improving production, trade, and distribution of food so that an increase in the quantity and quality of food would be available for all people. IFPRI has heightened its efforts to raise the awareness about emerging food security issues. In particular, its “2020 Vision for Food, Agriculture, and the Environment” initiative is aimed at promoting policy actions that will lead to food and nutrition security.